Residential Electric Load Curve Profile Based on Fuzzy Systems - Abreu, Thays [UNESP]; Alves, Uilian N. L. T. [UNESP]; Minussi, Carlos R. [UNESP]; Lotufo, Anna Diva P. [UNESP]; Lopes, Mara L. M. [UNESP]; IEEE (Ieee, 2015)
Electric energy demand in residences represents around 30% of the global demand. This requires a detailed knowledge about the electrical load patterns, leading to a change in final consumer behavior to reduce the general demand. This work uses a fuzzy system, considering the quantity of occupants in a Brazilian family in different periods of day aiming to obtain the residential electric load profile.
Keywords: Residential Load Curve; Active occupation; Fuzzy Logic